Analisis Kelayakan Usaha Keripik Singkong di Desa Kemuning Lor Kecamatan Arjasa Kabupaten Jember - Fuad Mustofa, Muhammad; Kurniawan, Deddy (Program Studi Agribisnis, 2024)
The agricultural sector is currently very popular among Indonesian people, so many business developments in the agricultural sector are starting to emerge. Currently, the business world, including agribusiness, is experiencing rapid change and growth. One of them is the development of food crop and horticultural businesses which has increased quite significantly, this can be seen from the increasing market demand for food crop and horticultural products. Gambirono Village is a community where the majority are farmers. Where farmers cultivate several crops such as rice, lime, salak, papaya, langsat, Siamese orange, and others. However, researchers are interested in researching Siamese oranges because recently Siamese oranges have only begun to be developed again, in recent years there have been several plants that have begun to be developed again, one of which is the Siamese orange plant. The selection of this research location was carried out deliberately or purposively. The data collection method uses primary data (interviews) secondary data (data obtained from sources directly related to the research). Based on the results of research using Rc Ratio analysis, it obtained a positive value or was feasible to carry out and for Feasibility analysis.